Islam, Slavery, and Racism: The Use of Strategy in the Pursuit of Human Rights (American Journal of Islam and Society, 1987)
Slavery is one of the most controversial and arresting topics in humanhistory. The question of Islam in relation to slavery has been an issue of concernamong scholars for a long time. It became a question in which manyOrientalists found a convenient gap to pass through in their attacks against thesystem of governance and justice in Islam. This self-righteous criticismagainst the attitude of Islam towards slavery is part of a long Western traditionof scholarship based on stereotyping, overstating, and selectivity of Islam inparticular and the Orient in general. Most of the time, the statements of thesescholars are presented in a sugar-coated style of language that is moredangerous than if they were presented in a critical, open, and direct language.Thomas Carlyle, Renan, Goldziher, Macdonald, von Grunebaum, Gibb andBernard Lewis are good examples and representatives of this traditi0n.lThe aim of this article is to use ijtihad, or informed intellectual effort, toshow through textual and historical evidence that Islam, in its battle forjustice, which is identical to human rights, fought against slavery and initiateda humane and practical plan for its abolition. Only deviation from Islamprevented elimination of slavery within the first few decades of Islam. InArabia itself within forty years, except for temporary prisoners of war,slavery had disappeared.We shall begin with a brief historical survey of the institution of slaverybefore Islam. The body of this article will concentrate on discussion andanalysis of some related texts from the Qufan and the Hadith as well as somehistorical data that reflect the practical attitude of devoted Muslims towardsslavery and slaves. The attitude of Islam towards race, color, and slavery inthe context of the trans-Saharan slave trade are two issues that this paper willdeal with since they have a direct bearing on the question of slavery in Islam ...